Chronic kidney disease-associated cardiovascular disease: scope and limitations of animal models. Issue 4 (December 2017) - Sadeghi-Alavijeh, Omid; Tadayyon, Mohammad; Caplin, Ben
Abstract : Chronic kidney disease (CKD) is a heterogeneous range of disorders affecting up to 11% of the world's population. The majority of patients with CKD die of cardiovascular disease (CVD) before progressing to end-stage renal disease. CKD patients have an increased risk of atherosclerotic disease as well as a unique cardiovascular phenotype. There remains no clear aetiology for these issues and a better understanding of the pathophysiology of CKD-associated CVD is urgently needed. Although nonanimal studies can provide insights into the nature of disease, the whole-organism nature of CKD-associated CVD means that high-quality animal models, at least for the immediate future, are likely to remain a key tool in improving our understanding in this area. We will discuss the methods used to induce renal impairment in rodents and the methods available to assess cardiovascular phenotype and in each case describe the applicability to humans.